Influence of Social Media on the Consumers’ Buying Behaviour - V. DHEENADHAYALAN,,; A. SANDEEP, (International Journal of Psychosocial Rehabilitation, 2020)
The social media platform is considered to be one of the most efficient ways in marketing brands online and attracting the customers. There is a high percentage of individual’s access to these platforms as soon as they awake. Social media are computer mediated technologies that facilitate the creation and sharing of information, ideas, career, interest and other forms of expressions via virtual communities and networks. The variety of stand-alone and build-in social media service currently available introduces challenges of definition. Social media use web based technologies, clerk top computer and mobile technologies to create highly interactive platforms through which individual, communities and organizations can share, co-create business and modify user generated content or pre-made content posted online. The social media became a very useful tool in buying decision making. It is influencing consumers in a dynamic manner. Now customer is taking help of social media regarding purchase of any product. Social media like Facebook, Twitter, Skype, etc. are going to play a very important role in consumers buying behaviour. So, the social medias are increasingly influencing and changing the way the consumers behave and how they make the decision to buy and the consumers’ behaviour depends upon their personality, attitude and the previous experiences.Thestudy focuses on the influences of social media on consumer buying behaviour with special reference to Malappuram and to know the awareness level of consumers towards social media. In addition, this study willidentify the relevance of social media to our society.